Poly(ionic liquid)s for Photo‐Driven CO2 Cycloaddition: Electron Donor–Acceptor Segments Matter. Issue 8 (15th January 2023) - Fang, Xu; Yang, Li; Dai, Zhangben; Cong, Die; Zheng, Daoyuan; Yu, Tie; Tu, Rui; Zhai, Shengliang; Yang, Junxia; Song, Fengling; Wu, Hao; Deng, Wei‐qiao; et al.
Abstract: CO2 cycloaddition with epoxides is a key catalytic procedure for CO2 utilization. Several metal‐based catalysts with cocatalysts are developed for photo‐driven CO2 cycloaddition, while facing difficulties in product purification and continuous reaction. Here, poly(ionic liquid)s are proposed as metal‐free catalysts for photo‐driven CO2 cycloaddition without cocatalysts. A series of poly(ionic liquid)s with donor–acceptor segments are fabricated and their photo‐driven catalytic performance (conversion rate of 83.5% for glycidyl phenyl ether) outstrips (≈4.9 times) their thermal‐driven catalytic performance (17.2%) at the same temperature. Mechanism studies confirm that photo‐induced charge separation is promoted by the donor–acceptor segments and can accelerate the CO2 cycloaddition reaction. This work paves the way for the further use of poly(ionic liquid)s as catalysts in photo‐driven CO2 cycloaddition. Abstract : Electron donor–acceptor (D‐A) segments are introduced into poly(ionic liquid)s (PILs) for the first time to expand their applications in photo‐driven CO2 cycloaddition. The promoted separation of photo‐induced carriers by D‐A segments in PILs, together with the photo‐induced thermal effect, boosts the efficient photo‐driven CO2 cycloaddition without metals, cocatalysts, and solvents.